Związek siły kończyn rozwijanej w warunkach statyki z ich masą mięśniową u studentek fizjoterapii = The relationship between limbs strength developed in static conditions and their mussle mass in women students of physiotherapy - Mroczkowski, Andrzej (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of the article was to determine the relationship between the sums of strengths and of bending and straightening moment strengths of the upper and lower limbs in static conditions and their muscle mass in women. The study involved 27 women students of physiotherapy, day-course, at Państwowa Wyższa Szkoła Zawodowa (State Higher Vocational School) in Konin. Strength measurements were performed using a tensometric dynamometer mounted on the supporting frame. The quantitative measurements of body composition were performed with the Tanita BC-148 Segmental Body Composition Analyzer.
Keywords: biomechanika; skład ciała; moment siły; biomechanics; body composition; moment strength